Analysis of Indonesia & Germany Cooperation on Urban Nexus Project in Support of Sdg's No 13 - Mochamad Imamuddinussalam; Deddy Muharman (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this research is to analyze the role of Indonesia and Germany cooperation in supporting the achievement of Sustainable Development Goals (SDGs) number 13 related to climate change, especially in the Urban Nexus project. This research uses a qualitative approach that is analytically descriptive. The research technique used is literature review. This research procedure consists of three steps: (1) preparation in determining the topic, (2) implementation in finding relevant reference sources, and writing down findings from various reference sources. The data was taken from the official websites of ESCAP, GIZ, and ICLEI that describe the Urban Nexus project, news, and research results published in journals. To obtain reliable data, triangulation technique was used as a data validity checking technique. The data analysis technique consists of three stages, namely data reduction, data presentation, and conclusion drawing. The results of the analysis found that the cooperation between Indonesia and Germany in the Urban Nexus project is a successful example of international cooperation in supporting SDG's through a holistic and integrative approach. Indonesia focuses on identifying prospects for Urban Nexus integration at the local and regional levels, integrating various aspects of the environment, infrastructure, supply chain, and services to avoid wasting assets. Meanwhile, Germany contributes with its expertise in technology and sustainable city management, assisting in the design and delivery of solutions, as well as training and operational capacity building